Prolixus (Acari: Trombidiformes: Tenuipalpidae) newly recorded from New Zealand: A new species from Cyperaceae and its ontogenetic patterns in chaetotaxy - Xu, Yun; Zhang, Zhi-Qiang (Zootaxa, 2014)
The genus Prolixus (Acari: Tenuipalpidae) was represented by two species from Australian sedges prior to this study. A new species, Prolixus meyerae sp. nov., is here described and illustrated from leaves of Gahnia (Cyperaceae) in Auckland, New Zealand. In this paper, we present the ontogenetic additions in idiosomal and leg chaetotaxy from larva to adult. A key to world species of Prolixus is also proposed.